Estudo sobre a influência de desgastes ondulatórios de trilhos no comportamento dinâmico de vagões ferroviários tipo gôndola - OLIVEIRA, Daniel Rodrigues (2016)
The rail transport is among one of the most widely used modes worldwide, both for cargo transport, as passenger. With the purpose of evaluating the dynamics behavior of railroad wagons gondola type in railways with quasi-periodic irregularities, it is developed a simplified multibody system with in order to mathematically represent the movements of the vehicle at the track excitations. The equations of motion were developed from the theories of Newton-Euler. The equations of motion was integrated with scientific computing software aid, by Runge-Kutta integration method. The results obtained by the program provide the displacements and velocities of bodies, as well as the forces resulting on wheels. The examination program is performed by comparing computer simulations results from other programs reported in the literature, where is witnessed that there are suitable correlations. The same vehicle is modeled using software for simulation of multibody systems. Through this it is possible to evaluate the interaction of forces in the wheel-rail contact, by means of the algorithm FASTSIM, and thus to obtain the tangential forces on the contacts. The results obtained by computer simulations demonstrate the influence of the caracteristics of irregularities in the way the dynamics behaviour of the vehicle and present interaction forces in the wheel-rail contact.